HYBRID ECOSYSTEMS AND INTELLIGENT EDGES: MAPPING THE EVOLUTION OF CLOUD COMPUTING IN THE COMING DECADE - Venkatakrishna Nukala , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive analysis of cloud computing trends and predictions for the decade 2024-2034, synthesizing current research and industry insights to forecast the evolution of cloud technologies and their impact on business operations. The article examines five key areas of development: the proliferation of hybrid and multi-cloud environments, the integration of artificial intelligence and machine learning into cloud services, the emergence of edge computing as a complement to centralized cloud infrastructures, enhanced focus on security and compliance in response to evolving cyber threats and regulatory landscapes, and the shift towards sustainable cloud computing practices. Through a systematic review of technological advancements and market dynamics, we argue that the next decade will witness a transformative convergence of these trends, fundamentally reshaping the cloud computing paradigm. Our findings suggest that organizations will need to adopt more flexible, intelligent, and environmentally conscious cloud strategies to remain competitive and compliant. This article contributes to the growing body of literature on cloud computing futures and provides valuable insights for business leaders, IT professionals, and policymakers navigating the rapidly changing digital landscape.